ANALYSIS OF STUDENTS’ LEARNING INTEREST BASED ON STUDENTS’ LEARNING ENVIRONMENT IN THE FACULTY OF EDUCATION - Riantina Fitra Aldya; Rio Febrianto Arifendi; Izzaini Nur Azizah Edward; Yulita Bangu Kahi (Universitas Tribhuwana Tunggadewi, 2025)
This study aims to determine the student’s perceptions about their learning interest based on learning environment. Data collection using a survey with a population of all 153 students of Biology and Mathematics Education in year of 2022, 2023 and 2024, with 108 students as sample using stratified random sampling. This survey is related to students perceptions about their learning interest with 5 aspects such as attention, curiosity, excitement, meaningfulness, and involvement from Mitchel (1993), that measured based on their learning environment including physical environment, social environment and the ease of their learning process. The results showed that learning interest is significantly influenced by three key aspects of the learning environment: physical surroundings, social environment, and the ease of the learning process. The physical environment, particularly environmental factors (57.4%), had the greatest effect on students’ attention (28,7%) and curiosity (23,1%) as comfortable, bright, and well-ventilated classrooms improved focus and engagement, then following with excitement (17,5%), meaningfulness (16,6%), and involvement (13,8%). The social environment, dominated by teacher–student interactions (37.9%), most strongly influenced involvement (36,1%) and excitement (28,7%), fostering motivation and a sense of belonging, then following with meaningfulness (13,8%), curiosity (12,9%), and finally students’ attention (8,3%). Meanwhile, the ease of the learning process, especially the clarity of material presentation (37.9%), enhanced attention (22,2%), then both meaningfulness and involvement (20,3%), lastly both curiosity and excitement (18,5%). So,it showed that a comfortable, interactive, and well-organized learning environment plays a crucial role in strengthening students’ learning interest.